Perennial Philosophy and Javanese Metaphysical Spirituality in Padepokan Kediri Garuda Nusantara - Diyananta Qonitya Salsabella; Ibnu Hajar Ansori (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to analyze the metaphysical foundations of Javanese spiritual traditions as practiced in the Padepokan Kediri Garuda Nusantara, employing Seyyed Hossein Nasr’s Perennial Philosophy as an interpretive framework. Javanese indigenous teachings such as Sangkan Paraning Dumadi, Kakang Kawah Adi Ari-ari, Sedulur Papat Limo Pancer, and Manunggaling Kawula Gusti articulate a spiritual quest that emphasizes self-realization as the pathway to divine knowledge and affirms the unity of ultimate reality. Rather than functioning merely as a site of ritual practice, the Padepokan embodies a metaphysical worldview that recognizes the One as manifested through diverse religious and cultural expressions. Using a qualitative research design, this study draws on in-depth interviews, institutional documentation, and textual analysis of Nasr’s perennial philosophy, supported by relevant scholarly literature. The findings demonstrate that the Padepokan Kediri Garuda Nusantara operates as a spiritual and socio-cultural space that bridges local metaphysical wisdom with discourses of global religious pluralism. By affirming the transcendent unity underlying religious diversity, the Padepokan contributes to the cultivation of interreligious moderation, ethical responsibility, and social harmony. This study argues that Nasr’s perennial philosophy provides a robust conceptual lens for understanding local spiritual traditions as integral components of universal and timeless metaphysical wisdom.